Industrial wastewater treatment using extracellular polymer substances/bioflocculants: a review - Bishwambhar Mishra; Parashuram Kallem; Rajasri Yadavalli; Sanjeeb Kumar Mandal; C. Nagendranatha Reddy; B. Sumithra; N. S. V Lakshmayya; Fawzi Banat (Applied Water Science)
Abstract The treatment of industrial wastewater, containing various contaminants like chemicals, dyes, and heavy metals, has emerged as a significant environmental issue. Traditional treatment procedures, although successful, frequently include synthetic chemicals that are non-biodegradable and present hazards to both ecosystems and human health. Bio-flocculants, especially those originating from extracellular polymeric substances (EPS) generated by microorganisms, provide an environmentally benign and sustainable option. These bioflocculants utilize microbial enzymes and polymeric substances to efficiently agglomerate and eliminate contaminants, adhering to the principles of green chemistry. Recent studies have concentrated on enhancing bioflocculant manufacturing technologies and their utilization in industrial wastewater treatment. Research is directed on improving biodegradability, cost-efficiency, and pollutant removal efficacy. This paper analyzes the function of microbial-based bioflocculants in industrial wastewater treatment, emphasizing their ecological advantages, biodegradability, and economic efficiency. It also examines progress in bioflocculant synthesis, concentrating on the production and application of EPS. Contemporary research trends focus on enhancing bioflocculant manufacturing technologies and broadening their industrial uses. Future initiatives focus on improving the efficiency and scalability of bioflocculants to facilitate new and sustainable wastewater management solutions.